Evasins: Therapeutic Potential of a New Family of Chemokine-Binding Proteins from Ticks - Bonvin, Pauline; Power, Christine A.; Proudfoot, Amanda E. I. (Frontiers in Immunology, 2016)
Blood sucking parasites such as ticks remain attached to their hosts for relatively long periods of time in order to obtain their blood meal without eliciting an immune response. One mechanism used to avoid rejection is the inhibition of the recruitment of immune cells, which can be achieved by a class of chemokine binding proteins (CKBPs) known as Evasins. We have identified three distinct Evasins produced by the salivary glands of the common brown dog tick, Rhipicephalus sanguineus. They display different selectivities for chemokines, the first two identified show a narrow selectivity profile, whilst the third has a broader binding spectrum. The Evasins showed efficacy in several animal models of inflammatory disease. Here we will discuss the potential of their development for therapeutic use, addressing both the advantages and disadvantages that this entails.